FinLearn: An Online Finance Learning Platform - Rizqullah, Wildan; Hasim, Nurdatillah (Journal of Computing Technologies and Creative Content, 2025)
The FinLearn is an online learning platform which developed to improve financial literacy among young adults in Malaysia. This approach implied self-paced learning on its online platform consists of progress tracking and personalization for users. Users can gain access to different courses and quizzes which allows them to learn more about personal finance topics such as debt management, savings, and more. The online learning platform is made available on the web to give easy access to the users from various backgrounds and locations. Programming languages used in this project include PHP, HTML, CSS, and JS with the aid of development tools such as Visual Studio, Code, Laragon, Github, Microsoft 365, and Firefox via MySQL database. Besides, FinLearn is expected to benefit users by enabling them to keep engaged in finance learning digitally interactively, as well as allowing them to track their progress and adjust their learning strategies. Hence, this abstract is focus in outlining the online learning platform’s functions and emphasizing the roles and benefits of FinLearn in improving financial literacy among Malaysian young adults